Evaluasi Kesesuaian Lahan untuk Komoditas Tanaman Karet (Hevea Brasilliensis) dengan Menggunakan Fuzzy Logic di Kecamatan Padang Sago Kabupaten Padang Pariaman Provinsi Sumatera Barat - Nurkhairani, Poppy; Triyatno, Triyatno (Al-DYAS, 2025)
The purpose of this research are: 1) The objective of this study is to map the locations of rubber plantations found in Padang Sago District, Padang Pariaman Regency, 2) To analyze the characteristics of land for rubber plantations in Padang Sago District, Padang Pariaman Regency, 3) To analyze the suitability of potential land for rubber plantations in Padang Sago District, Padang Pariaman Regency. This study employs a quantitative approach using the fuzzy logic method to analyze land suitability and a location plotting technique with GIS to map the rubber plantations. Based on the results of research and data processing, it was found: 1) Rubber plantations in Kecamatan Padang Sago are located in Nagari Koto Dalam Selatan and Nagari Batu Kalang due to suitable topography, appropriate rainfall, fine soil texture, and good soil drainage. 2) Characteristics of rubber plantations for rainfall indicators ranging from 3,100–3,500mm/yr, soil drainage categorized as good and obstructed. The soil texture found in the research area is rough and fine. Soil depth ranges from 75cm-100cm and >100 cm. Cation Exchange Capacity (CEC) includes low and medium. Meanwhile, soil acidity (pH) has a value of 4.5-5.0. including sour and very sour, 3) The suitability of the land for rubber plantations obtained using fuzzy logic analysis obtained the area for the land suitability index value in the category not to less than suitable 0 - 0.59 has an area of 1,947.64 Ha with a percentage of 55.29% and for the index category quite suitable to suitable 0.6 – 0.79 has an area of 1,575.26 Ha with a percentage of 44.71%.